Hypomethylation of the aquatic invasive plant, Ludwigia grandiflora subsp. hexapetala mimics the adaptive transition into the terrestrial morphotype. Issue 2 (16th August 2020) - Genitoni, Julien; Vassaux, Danièle; Delaunay, Alain; Citerne, Sylvie; Portillo Lemus, Luis; Etienne, Marie‐Pierre; Renault, David; Stoeckel, Solenn; Barloy, Dominique; Maury, Stéphane
Abstract : Ongoing global changes affect ecosystems and open up new opportunities for biological invasion. The ability of invasive species to rapidly adapt to new environments represents a relevant model for studying short‐term adaptation mechanisms. The aquatic invasive plant, Ludwigia grandiflora subsp. hexapetala, is classified as harmful in European rivers. In French wet meadows, this species has shown a rapid transition from aquatic to terrestrial environments with emergence of two distinct morphotypes in 5 years. To understand the heritable mechanisms involved in adjustment to such a new environment, we investigate both genetic and epigenetic as possible sources of flexibility involved in this fast terrestrial transition. We found a low overall genetic differentiation between the two morphotypes arguing against the possibility that terrestrial morphotype emerged from a new adaptive genetic capacity. Artificial hypomethylation was induced on both morphotypes to assess the epigenetic hypothesis. We analyzed global DNA methylation, morphological changes, phytohormones and metabolite profiles of both morphotype responses in both aquatic and terrestrial conditions in shoot and root tissues. Hypomethylation significantly affected morphological variables, phytohormone levels and the amount of some metabolites. The effects of hypomethylation depended on morphotypes, conditions and plant tissues, which highlighted differences among the morphotypes and their plasticity. Using a correlative integrative approach, we showed that hypomethylation of the aquatic morphotype mimicked the characteristics of the terrestrial morphotype. Our data suggest that DNA methylation rather than a new adaptive genetic capacity is playing a key role in L. grandiflora subsp. hexapetala plasticity during its rapid aquatic to terrestrial transition.